Controlling seepage in discrete particle simulations of biological systems. Issue 11 (17th August 2016) - Gardiner, Bruce S.; Joldes, Grand R.; Wong, Kelvin K. L.; Tan, Chin Wee; Smith, David W.
Abstract: It is now commonplace to represent materials in a simulation using assemblies of discrete particles. Sometimes, one wishes to maintain the integrity of boundaries between particle types, for example, when modelling multiple tissue layers. However, as the particle assembly evolves during a simulation, particles may pass across interfaces. This behaviour is referred to as 'seepage'. The aims of this study were (i) to examine the conditions for seepage through a confining particle membrane and (ii) to define some simple rules that can be employed to control seepage. Based on the force-deformation response of spheres with various sizes and stiffness, we develop analytic expressions for the force required to move a 'probe particle' between confining 'membrane particles'. We analyse the influence that particle's size and stiffness have on the maximum force that can act on the probe particle before the onset of seepage. The theoretical results are applied in the simulation of a biological cell under unconfined compression.